High speed parametric processing controlled by few photons. (November 2015) - Pejkic, Ana; Radic, Stojan
Abstract: Optical signal processing has long been recognized as a promising route to a new class of fast and energy efficient devices. The former parameter, the speed, has indeed been addressed in a number of different signal processing roles, confirming the superiority of optical signal processing devices with respect to their electronic counterpart. After gaining some maturity, the field has now advanced to reducing the energy consumption. In this regard, new efforts are directed toward designing an efficient photon interaction mediator, expected to provide both fast and energy efficient devices. The key topic of this review is the progress in longitudinal silica fiber dispersion engineering enabling efficient, non-reciprocal parametric mixers. We present how longitudinal dispersion fluctuations, once considered detrimental, can now be exploited to alter the phase matching condition, and thus, enable fast control of a high power beam by few photons. The potential of such a functionality in high-speed optical signal processing and sensing is discussed.